Guide to microsimulations linked to CGE models: How to introduce analysis of poverty and income distribution in CGE-based studies - Estrades, Carmen (International Food Policy Research Institute, 2013)
Micro-macro syntheses have become a powerful tool to capture the micro effects of macro policies and external shocks on income distribution and poverty. The range of techniques is wide and their implementation will depend on the objectives of the study, the availability of time and data, and the compatibility with the macro model applied. This guide presents the different techniques and briefly describes their pros and cons. It also presents detailed instructions on how to implement two microsimulation techniques: a non-parametric microsimulation model and a representative household model. In order to illustrate both methods, a specific application to Tanzania is presented.